Even in the rain : Uyghur music in modern China - Wong, Chuen-Fung, 1977- (Music and performing arts of Asia and the Pacific., 2023)
"Even in the Rain: Uyghur Music in Modern China explores music as constitutive of Uyghur cultural and social life where subaltern experiences of ethnicity, race, and nationhood are indexed. A Central Asian Turkic-speaking, predominantly Muslim people, the Uyghur are identified in China as one of the fifty-five officially designated "minority nationalities." Drawing on extensive fieldwork in the Uyghur homeland in the far Chinese northwest, Chuen-Fung Wong focuses on aspects of Uyghur music making as it faces the state's management of minority art expressions. Music serves as a metaphor of the Uyghur nation-as heritage (miras), culture (medeniyet), and tradition (en'ene)-while it struggles to survive, respond, and adapt to the Chinese state's aggressive maneuvering and the broader intercultural influences that have shaped Uyghur performing arts in modern times. As the Uyghur and other non-Han peoples in China continue to be minoritized under the pretexts of multiculturalism and cultural enlightenment, local musicians and audiences react with a vast range of performing and listening approaches to engage assimilation, racism, and other grim realities of everyday life. Even in the Rain provides the political, historical, and theoretical context to address overlapping genres and soundscapes, which are bound by creative processes that have negotiated the state's minority policy and the collective pursuit of identity. With a focus on the minoritized musical consciousness in Uyghur performance, especially on the ways in which Uyghur musicians encounter modernity under a colonial context, this book examines the cultivation of a unique musical deftness that has allowed musicians to move across the various localizing strategies and intercultural practices. Uyghur musical modernity should not be understood as the passive acceptance of outside influences-and certainly not the erasure of indigenous elements and national heritage. Local traditions and hegemonic influences sometimes appear to be more collaborating than conflicting, in that subaltern expressions actively opt to manifest in forms that are dominant and deemed universal. This timely and comprehensive analysis spans approximately seven decades of modern Uyghur musical life, during which musicians and audiences adopted an array of methods, experimenting with new identity formations to navigate life as often reluctant Chinese citizens"--